The Role of Financial Knowledge and Attitudes in Financial Management Through Financial Planning at Beverage MSMEs in Jepara - Defita Na'Imah; Anna Widiastuti (TALENTA Publisher, Universitas Sumatera Utara, 2026)
This study aims to analyze the influence of financial knowledge and financial attitude on financial management through the mediating role of financial planning among beverage MSMEs in Jepara Regency. The research uses a quantitative approach with 126 respondents selected through simple random sampling. Data were collected using questionnaires distributed directly and via Google Forms, then analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with SmartPLS 3.0. The results show that financial knowledge has a positive and significant effect on both financial planning and financial management, while financial attitude has a positive and significant effect on financial planning but not directly on financial management. Financial planning has a positive and significant effect on financial management and mediates the relationships between financial knowledge and financial attitude toward financial management. These findings indicate that improving financial literacy and fostering a positive financial attitude can enhance financial management performance when supported by structured financial planning. The study contributes to understanding the financial behavior of MSME entrepreneurs and provides practical implications for business owners and policymakers to design training programs that strengthen financial knowledge, attitudes, and planning to ensure the sustainability and competitiveness of small enterprises. Keyword: Financial Knowledge, Financial Attitude, Financial Planning, Financial Management, MSMEs